Prevalence and risk factors of Low Birth Weight in Fars province, south of Iran, 2014 - Alireza Mirahmadizadeh; Ali Soleimani; Fariba Moradi; Elham Hesami; Maryam Kasraeian; Hamed Delam (Shiraz University of Medical Sciences, 2017)
Background/Objective: This study was conducted to assess the prevalence of low birth weight and its risk factors in Fars province, south of Iran, 2014. Methods: In this cross-sectional study, we collected data of 3,600 neonates through multi-stage random sampling. At first, we divided the hospitals into two strata, private and public. Then by stratified random sampling, we selected the neonates from delivery list in each hospital. In univariate analysis, the variables in which the p-value was less than 0.2 were entered into multivariate logistic regression analysis model for adjusting. Two-sided p values <0.05 were statistically considered significant. Result: The prevalence of low birth weight in Fars province was 8.7% (95% CI: 7.8% - 9.7%). In term birth, factors such as mother's age > 35 years, multiple birth and duration < 24 months with previous pregnancy were risk factors of low birth weight (P <0 .05) and just the father's literacy was a protective factor for low birth weight. Conclusion: The prevalence of low birth weight in Fars province was low in comparison to that of the world and other districts of Iran. But we should plan for reduction of low birth weight to achieve world health organization's goal. Variables of pregnancy interval of less than 2 years, multiple births, mother's age over 35 years and father's level of education could predict low birth weight of the neonates.